2017
DOI: 10.1186/s12877-017-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a frailty index from the resident assessment instrument – home care adapted for Switzerland: a study based on retrospective data analysis

Abstract: BackgroundThe screening of frail individuals at risk for functional health decline and adverse health outcomes lies in the evolving agenda of home care providers. Such a screening can be based on a frailty index (FI) derived from data collected with interRAI instruments used in clinical routines to define care plans. The objective of this study was to assess the feasibility of deriving an FI from the Resident Assessment Instrument – Home Care adapted for Switzerland (Swiss RAI-HC).MethodsData were collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
(84 reference statements)
0
21
2
1
Order By: Relevance
“…In Ludwig and Busnel's study of home medical care in Switzerland, patients with a higher frailty score had a higher chance of an unplanned hospitalization (OR 3.40, 95% CI 1.78-6.32) when compared with low frailty score patients. 21 Comparatively, the present participants were frailer (mean FI 0.34 AE 0.11) than the previous study population (mean FI 0.24 AE 0.13). We hypothesize that in frailer populations, the DSS is a stronger predictor of unplanned hospitalizations than frailty itself, and should be included in the management of this group of patients.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In Ludwig and Busnel's study of home medical care in Switzerland, patients with a higher frailty score had a higher chance of an unplanned hospitalization (OR 3.40, 95% CI 1.78-6.32) when compared with low frailty score patients. 21 Comparatively, the present participants were frailer (mean FI 0.34 AE 0.11) than the previous study population (mean FI 0.24 AE 0.13). We hypothesize that in frailer populations, the DSS is a stronger predictor of unplanned hospitalizations than frailty itself, and should be included in the management of this group of patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Some previous investigations of risk factors for unplanned hospitalizations reported that frailty was an independent predictor of hospitalization in home medical care. In Ludwig and Busnel's study of home medical care in Switzerland, patients with a higher frailty score had a higher chance of an unplanned hospitalization (OR 3.40, 95% CI 1.78–6.32) when compared with low frailty score patients . Comparatively, the present participants were frailer (mean FI 0.34 ± 0.11) than the previous study population (mean FI 0.24 ± 0.13).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…A cut point of FI > 0.21 is preferred for studies conducted in community-based population [27][28][29][30][31][32]. A FI can be computed from routinely collected health data, whether from CGAs [26,33,34], primary care electronic health records [35] or minimum datasets [MDS] gathered with Resident Assessment Instruments (RAI) [36,37] designed for acute care [38][39][40], home care [29,[41][42][43][44] and nursing homes [45]. The rationale underlying deriving the FI from clinical datasets is to provide a measure of frailty that demonstrates substantial agreement across studies [25,46] and high predictive validity of undesirable health outcomes [47,48].…”
Section: Introductionmentioning
confidence: 99%